Assessing the impacts of tillage and fertilization management on nitrous oxide emissions in a cornfield using the DNDC model. Issue 2 (5th February 2016) - Deng, Qi; Hui, Dafeng; Wang, Junming; Yu, Chih‐Li; Li, Changsheng; Reddy, K. Chandra; Dennis, Sam
Abstract: Quantification and prediction of N2 O emissions from croplands under different agricultural management practices are vital for sustainable agriculture and climate change mitigation. We simulated N2 O emissions under tillage and no‐tillage, and different nitrogen (N) fertilizer types and application methods (i.e., nitrification inhibitor, chicken manure, and split applications) in a cornfield using the DeNitrification‐DeComposition (DNDC) model. The model was parameterized with field experimental data collected in Nashville, Tennessee, under various agricultural management treatments and run for a short term (3 years) and a long term (100 years). Results showed that the DNDC model could adequately simulate N2 O emissions as well as soil properties under different agricultural management practices. The modeled emissions of N2 O significantly increased by 35% with tillage, and decreased by 24% with the use of nitrification inhibitor, compared with no‐tillage and normal N fertilization. Chicken manure amendment and split applications of N fertilizer had minor impact on N2 O emission in a short term, but over a long term (100 years) the treatments significantly altered N2 O emission (+35%, −10%, respectively). Sensitivity analysis showed that N2 O emission was sensitive to mean annual precipitation, mean annual temperature, soil organic carbon, and the amount of total N fertilizer application. Our model results provide valuable information for determining agricultural best management practice to maintain highly productive corn yield while reducing greenhouse gas emissions. Key Points: The DNDC model is applied to simulate N2 O emission under various agricultural management practices Modeled N2 O emission is increased by tillage and decreased by the use of nitrification inhibitor Modeled N2 O emission is sensitive to rainfall, temperature, soil carbon, and fertilizer amount